Preprinting is positively associated with early career researcher status in ecology and evolution. Issue 20 (21st September 2021) - Wolf, Jesse F.; MacKay, Layla; Haworth, Sarah E.; Cossette, Marie‐Laurence; Dedato, Morgan N.; Young, Kiana B.; Elliott, Colin I.; Oomen, Rebekah A.
Abstract: The usage of preprint servers in ecology and evolution is increasing, allowing research to be rapidly disseminated and available through open access at no cost. Early Career Researchers (ECRs) often have limited experience with the peer review process, which can be challenging when trying to build publication records and demonstrate research ability for funding opportunities, scholarships, grants, or faculty positions. ECRs face different challenges relative to researchers with permanent positions and established research programs. These challenges might also vary according to institution size and country, which are factors associated with the availability of funding for open access journals. We predicted that the career stage and institution size impact the relative usage of preprint servers among researchers in ecology and evolution. Using data collected from 500 articles (100 from each of two open access journals, two closed access journals, and a preprint server), we showed that ECRs generated more preprints relative to non‐ECRs, for both first and last authors. We speculate that this pattern is reflective of the advantages of quick and open access research that is disproportionately beneficial to ECRs. There is also a marginal association between first author, institution size, and preprint usage, whereby the number of preprints tends to increase with institution size for ECRs. The United States and United Kingdom contributed the greatest number of preprints by ECRs, whereas non‐Western countries contributed relatively fewer preprints. This empirical evidence that preprint usage varies with the career stage, institution size, and country helps to identify barriers surrounding large‐scale adoption of preprinting in ecology and evolution. Abstract : We predicted that the career stage and institution size would impact the relative usage of preprint servers among researchers in ecology and evolution. Using data collected from 500 articles, we demonstrate that ECRs generate more preprints relative to non‐ECRs, for both first and last authors. We speculate that this pattern is reflective of the advantages of quick and open access research that is disproportionately beneficial to ECRs.